Single-cell chromatin accessibility profiling of cell-state-specific gene regulatory programs during mouse organogenesis - Deng, Qiuting; Wang, Shengpeng; Huang, Zijie; Lan, Qing; Lai, Guangyao; Xu, Jiangshan; Yuan, Yue; Liu, Chang; Lin, Xiumei; Feng, Weimin; Ma, Wen; Cheng, Mengnan; et al. (Frontiers in Neuroscience, 2023)
In mammals, early organogenesis begins soon after gastrulation, accompanied by specification of various type of progenitor/precusor cells. In order to reveal dynamic chromatin landscape of precursor cells and decipher the underlying molecular mechanism driving early mouse organogenesis, we performed single-cell ATAC-seq of E8.5-E10.5 mouse embryos. We profiled a total of 101,599 single cells and identified 41 specific cell types at these stages. Besides, by performing integrated analysis of scATAC-seq and public scRNA-seq data, we identified the critical cis-regulatory elements and key transcription factors which drving development of spinal cord and somitogenesis. Furthermore, we intersected accessible peaks with human diseases/traits-related loci and found potential clinical associated single nucleotide variants (SNPs). Overall, our work provides a fundamental source for understanding cell fate determination and revealing the underlying mechanism during postimplantation embryonic development, and expand our knowledge of pathology for human developmental malformations.